Evaluating the impact of Industry 4.0 technologies on medical devices manufacturing firm's operations during COVID-19. (6th October 2022) - Narula, Sanjiv; Prakash, Surya; Puppala, Harish; Dwivedy, Maheswar; Talwar, Vishal; Singh, Rajinder
There is a strong opinion about the impact of Industry 4.0 (I4.0) technologies on the operations performance of manufacturing firms. However, there are several challenges while evaluating such situations. Determining the significance of I4.0 technologies in the context of the pandemic situation must consider several criteria for exhaustive understanding. This study aims to determine the significance and impact of I4.0 technologies on medical devices manufacturing firms' operations during the COVID-19 outbreak. The set of technologies of I4.0 is evaluated over productivity, quality, cost, delivery, health, and safety parameters using a fuzzy analytical hierarchy process. The study reveals that the significance of big data analytics, autonomous robotics, and industrial internet of things (IIoT) in the business continuity of medical device manufacturing operations during the COVID-19 outbreak is high. Cloud technologies, digital simulations and augmented reality follow the order.